A Single Oxidosqualene Cyclase Produces the Seco-Triterpenoid α-Onocerin . Issue 2 (4th December 2017) - Almeida, Aldo; Dong, Lemeng; Khakimov, Bekzod; Bassard, Jean-Etienne; Moses, Tessa; Lota, Frederic; Goossens, Alain; Appendino, Giovanni; Bak, Søren
Abstract : In Ononis spinosa, a single oxidosqualene cyclase interacts with squalene epoxidases to produce α-onocerin from squalene dioxide, demonstrating that α-onocerin pathways evolved convergently in plants. Abstract: 8, 14- seco -Triterpenoids are characterized by their unusual open C-ring. Their distribution in nature is rare and scattered in taxonomically unrelated plants. The 8, 14- seco -triterpenoid α-onocerin is only known from the evolutionarily distant clubmoss genus Lycopodium and the leguminous genus Ononis, which makes the biosynthesis of this seco -triterpenoid intriguing from an evolutionary standpoint. In our experiments with Ononis spinosa, α-onocerin was detected only in the roots. Through transcriptome analysis of the roots, an oxidosqualene cyclase, OsONS1, was identified that produces α-onocerin from squalene-2, 3;22, 23-dioxide when transiently expressed in Nicotiana bethamiana . In contrast, in Lycopodium clavatum, two sequential cyclases, LcLCC and LcLCD, are required to produce α-onocerin in the N. benthamiana transient expression system. Expression of OsONS1 in the lanosterol synthase knockout yeast strain GIL77, which accumulates squalene-2, 3;22, 23-dioxide, verified the α-onocerin production. A phylogenetic analysis predicts that OsONS1 branches off from specific lupeol synthases and does not group with the known L. clavatum α-onocerin cyclases. Both the biochemical and phylogenetic analyses of OsONS1 suggest convergent evolution of the α-onocerin pathways. When OsONS1 was coexpressed in N. benthamiana leaves with either of the two O. spinosa squalene epoxidases, OsSQE1 or OsSQE2, α-onocerin production was boosted, most likely because the epoxidases produce higher amounts of squalene-2, 3;22, 23-dioxide. Fluorescence lifetime imaging microscopy analysis demonstrated specific protein-protein interactions between OsONS1 and both O. spinosa squalene epoxidases. Coexpression of OsONS1 with the two OsSQE s suggests that OsSQE2 is the preferred partner of OsONS1 in planta. Our results provide an example of the convergent evolution of plant specialized metabolism.